An Option-Based Approach to Bank Vulnerabilities in Emerging Markets - Jobert, Arnaud (IMF Working Papers; Working Paper ;, 2004)
We measure bank vulnerability in emerging markets using the distance-to-default, a risk-neutral indicator based on Merton's (1974) structural model of credit risk. The indicator is estimated using equity prices and balance-sheet data for 38 banks in 14 emerging market countries. Results show it can predict a bank's credit deterioration up to nine months in advance. The distance-to-default, hence, may prove useful for bank monitoring purposes.